IMPLEMENTASI KONSEP TPACK (TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE) DALAM PEMBELAJARAN EVALUASI PENDIDIKAN DI SEKOLAH TINGGI AGAMA ISLAM RAHMANIYAH SEKAYU - Jusma, Litado Dewi; Ermalinda, Ermalinda; Husni, Hafizul; Anggraini, Atika (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
This study aims to examine the implementation of the TPACK (Technological Pedagogical Content Knowledge) concept in the Educational Evaluation learning process at Sekolah Tinggi Agama Islam Rahmaniyah Sekayu, with a sample of 38 students. The TPACK concept integrates knowledge of technology, pedagogy, and content to enhance the effectiveness of the learning process. The research model employs an empirical approach with data analysis techniques according to Miles and Huberman, which include data collection, data reduction, data presentation, and conclusion drawing. Data were collected through observations, interviews, and questionnaires administered to 38 students enrolled in the Educational Evaluation course. The results show that the implementation of TPACK in teaching has been effective, with students giving positive responses to the use of technology in understanding educational evaluation materials. However, there are several challenges related to the limited understanding of students regarding technology use and the mismatch between pedagogical techniques and the technology implemented. Based on the findings, it is recommended that instructors enhance their technological skills and provide more training for students to ensure optimal integration of technology in learning.